Evaluation of High-Pressure Processing in Inactivation of the Hepatitis E Virus - Nasheri, Neda; Doctor, Tanushka; Chen, Angela; Harlow, Jennifer; Gill, Alexander (Frontiers in Microbiology, 2020)
Hepatitis E virus (HEV) causes acute hepatitis with approximately 20 million cases per year globally. Based on genetic diversity, HEV is classified into different genotypes, with genotype 3 (HEV-3) being most prevalent in Europe and North America. The transmission of HEV-3 has been shown to be zoonotic and mainly associated with the consumption of raw or undercooked pork products. Herein, we investigated the efficacy of high-pressure processing (HPP) in inactivation of HEV-3 using a cell culture system. HPP has been indicated as a promising nonthermal pathogen inactivation strategy for treatment of certain high-risk food commodities, without any noticeable changes in their nature. For this purpose, we treated HEV-3 in media with different conditions of HPP: 400 MPa for 1 and 5 minutes, as well as 600 MPa for 1 and 5 minutes, at ambient temperature. All four HPP treatments of HEV in media were observed to result in a 2-log reduction in HEV load, as determined by the amounts of extracellular HEV RNA produced at 14-day post infection, using the A549/D3 cell culture system. However, application of the same treatments to artificially contaminated pork pâté resulted in 0.5 log reduction in viral load. These results indicate that the efficacy of HPP treatment in the inactivation of HEV-3 is matrix-dependent, and independent of maximum pressure between 400 and 600 MPa and hold time between 1 and 5 min. Based on the obtained results, although the HPP treatment of pork pâté reduces the HEV-3 load, it might not be sufficient to fully mitigate the risk.